Bypassing the financial growth cycle: Evidence from Capital Pool Companies - Carpentier, Cécile; Suret, Jean-Marc (Journal of Business Venturing, 2006)
To close a putative equity gap, Canadian regulators implemented the Capital Pool Company program, which enables small firms to directly access the stock market, thus bypassing the conventional growth cycle. Capital Pool Companies spawned more than half of the initial issues on Canadian stock markets between 1995 and 2001. Three postulates underlie this program: 1) a significant number of profitable companies cannot be financed by conventional tools, 2) small firms can grow and succeed without the full range of services offered by conventional funding providers, and 3) individual investors are able to correctly price the stocks issued by small, generally young firms. Our analysis of close to 450 issuers resulting from this program fails to confirm any of these postulates. As a public policy, the development of mechanisms intended to facilitate the entry of emerging companies on the stock market requires serious reexamination. Our results confirm the critical role of conventional funding providers in small business finance.